Aberrant cortico-thalamic structural connectivity in premature-born adults. (August 2021) - Menegaux, Aurore; Meng, Chun; Bäuml, Josef G.; Berndt, Maria T.; Hedderich, Dennis M.; Schmitz-Koep, Benita; Schneider, Sebastian; Nuttall, Rachel; Zimmermann, Juliana; Daamen, Marcel; Zimmer, Claus; Boecker, Henning; et al.
Abstract: Premature birth is associated with alterations in brain structure, particularly in white matter. Among white matter, alterations in cortico-thalamic connections are present in premature-born infants, and they have been suggested both to last until adulthood and to contribute to impaired cognitive functions. To test these hypotheses, 70 very premature-born adults and 67 full-term controls underwent cognitive testing and diffusion-weighted imaging. Each cortical hemisphere was parcellated into six lobes, from which probabilistic tractography was performed to the thalamus. Connection probability was chosen as metric of structural connectivity. We found increased cortico-thalamic connection probability between left prefrontal cortices and left medio-dorsal thalamus and reduced connection probability between bilateral temporal cortices and bilateral anterior thalami in very premature-born adults. Aberrant prefronto- and temporo-thalamic connection probabilities were correlated with birth weight and days on ventilation, respectively, supporting the suggestion that these connectivity changes relate with the degree of prematurity. Moreover, an increase in left prefronto-thalamic connection probability also correlated with lower verbal comprehension index indicating its relevance for verbal cognition. Together, our results demonstrate that cortico-thalamic structural connectivity is aberrant in premature-born adults, with these changes being linked with impairments in verbal cognitive abilities. Due to corresponding findings in infants, data suggest aberrant development of cortico-thalamic connectivity after premature birth with lasting effects into adulthood.